Experimental Study of Single Stage Centrifugal Pump Characteristics and Cussons Friction Loss Apparatus - Kania Amelia Safitri; Sutardi Sutardi (JMES: The International Journal of Mechanical Engineering and Sciences, 2019)
Water is a primary need for human life. Because of its important use, an integrated system was built consisting of pumps and pipes to distribute water. The phenomenon of energy loss is found in the process of distributing water using pumps and pipes. To understand the energy loss phenomenon that occurs, an experimental test is carried out on a piping installation. Fluid mechanics and turbomachinery laboratories have experimental test equipment in the form of CUSSONS friction loss in pipe apparatus with a single-stage centrifugal pump to study the energy loss phenomenon that occurs in piping installations. This test equipment is composed of two kinds of pipe materials, namely PVC and acrylic, with variations in pipe diameter of 0.75 and 1.0 inch, flow meters in the form of venturi and orifice, pipe fittings in the form of elbow 45°, long radius elbow 90°, short radius elbow 90°, a valve in the form of ball-valve and pump connected to the NEWMAN electric motor which has a power of 1.5 HP and a rotational speed of 2850 RPM. The pressure drop in the piping installation was measured using a mercury manometer, the increase in pump pressure was measured with a pressure gauge, and the current and voltage of the motor pump were measured using a clamp meter. The flow rate for the installation was varied between 10L/min to 55 L/min with an increase in the flow rate of 5 L/min for the data collection on straight-pipe line I, fittings, and ball valves, on straight-pipe line II the variation of discharge only reached 40 L/min, while the variation of discharge for the flow meters was from 10 L/min to 30 L/min with an increase in the flow rate of 2 L/min for the orifice and 4 L/min for the venturi. Based on the experimental test data, it was found that the loss coefficient value (Kl) for K90= 0.58, for K45= 0.38, KBV = 0.62, and KLRE= 0.611. Relative roughness (e/D) on pipe line I= 0.0043 and pipe line II = 0.024. The coefficient of discharge (Cd) on the venture-type flow meter Ce= 0.91 and Co= 0.72 at maximum discharge. Maximum pump efficiency (ηp) was 27.1% when the pump head= 18.79 m.